Outcomes of Kidney Transplantation from Circulatory Death Donors With Increased Terminal Creatinine Levels in Serum. Issue 7 (July 2016) - Tomita, Yusuke; Tojimbara, Tamotsu; Iwadoh, Kazuhiro; Nakajima, Ichiro; Fuchinoue, Shohei
Abstract : Background: To alleviate chronic renal graft shortages in Japan, donation after circulatory death (DCD) is an increasingly used organ resource. Organs from DCD donors with progressively increased terminal creatinine (t-Cr) levels are frequently used, but the effects of this condition on kidney transplantation (KTx) remain unclear. Methods: Between 1996 and 2013, 99 KTx from DCD donors were conducted in our department. Recipients were grouped according to the t-Cr (in mg/dL) of donors: group 1, t-Cr less than < 1.5; group 2, 1.5 ⩽ t-Cr < 3.0; and group 3, t-Cr ≥ 3.0. We analyzed the long-term outcomes of KTx from DCD donors retrospectively in terms of donors' terminal renal function. Results: The respective mean donor t-Cr in groups 1, 2, and 3 were 0.73 ± 0.28, 2.02 ± 0.40, and 6.69 ± 3.68. The respective death-censored graft survival rates (%) in groups 1, 2, and 3 were 90.2, 96.2, and 86.7 at 1 year and 70.3, 86.2, and 73.4 at 10 years after transplantation. Group 1 exhibited lower incidence of delayed graft function than either group 2 or group 3 (80.5% vs 100% and 93.3%). Nevertheless, no significant difference was found between groups for several measures: Cr levels 1 month after KTx and lowest Cr levels throughout the observation period, prevalence of biopsy-proven acute rejection, and graft survival. Cox proportional hazard regression showed that donor age, cerebrovascular event, terminal urine output, and history of hypertension were significantly associated with graft survival. Conclusions: Results suggest that, under certain conditions, kidneys from DCD donors with progressively increased t-Cr can be used safely with promising long-term outcomes. Abstract : Kidneys from donation after circulatory death donors with a high terminal creatinine levels can be used safely with promising long-term outcomes although donor age, cerebrovascular event, terminal urine output, and history of hypertension are significantly associated with graft survival. Supplemental digital content is available in the text.